Impact of ultrasound and potassium chloride on the physicochemical and sensory properties in low sodium restructured cooked ham. (July 2020) - Barretto, Tiago Luis; Bellucci, Elisa Rafaela Bonadio; Barbosa, Roger Darros; Pollonio, Marise Aparecida Rodrigues; Romero, Javier Telis; da Silva Barretto, Andrea Carla
Abstract: The objectives of this study were to evaluate the effects of power ultrasound (nominal intensity 600 W·cm −2 for 10 min) and the addition of potassium chloride (KCl) on the physicochemical properties and sensorial acceptance of low sodium restructured cooked ham. Four treatments of low sodium restructured cooked ham (mean of 324.52 mg Na/100 g) were prepared: CT - Control Treatment; UsT - Ultrasound Treatment; KT - addition of 0.5% KCl; UsKT - Ultrasound Treatment and addition of 0.5% KCl. Ultrasound application reduced the total fluid released and improved the sensory acceptance for salty taste and flavor compared to CT. The addition of KCl showed the lowest values for total fluid release, the highest scores for all parameters of sensory acceptance, improved hardness and chewiness, which results were not statistically different from the results obtained by combining ultrasound and KCl. Therefore, the use of KCl was considered a technological and sensorial viable alternative to produce low sodium restructured cooked ham. Chemical compounds used in this research: Methanol (PubChem CID: 887); Chloroform (PubChem CID: 6212); Sodium Carbonate (PubChem CID: 10340); Sodium hydroxide (PubChem CID: 14798); Boric acid (PubChem CID: 7628). Highlights: Ultrasound and potassium chloride were used in processing low sodium restructured cooked ham. Ultrasound improved the total fluid release, the flavor and overall acceptance. The addition of potassium chloride was more effective than the use of ultrasound for the physicochemical and sensory parameters. The combination of ultrasound and the addition of potassium chloride showed no additional benefit.